CARACTÉRISATION PHYSIOLOGIQUES DE DIX ACCESSIONS DE JATROPHA CURCAS DANS DEUX ZONES PÉDOCLIMATIQUES ASSEZ CONTRASTÉES DE LA CÔTE D’IVOIRE - Coulibaly Noupé Diakaria; Kone Mongomaké; Soro Dogniméton; Kouadio Yatty Justin (European Scientific Journal, ESJ, 2015)
Jatropha curcas an oleaginous plant of the Euphorbiaceae family is still wild in Côte d’Ivoire. This plant has many uses including the manufacture of biofuels. Domestication aims to select the accessions expressing good growth and therefore adapted to a particular area. Jatropha curcas accessions have been collected in ten towns in Côte d’Ivoire. These were grown on soils of land located in the South and North. The experiment was laid out in a random complete block design. The physiological characteristics were determined from the vegetative growth of the plants. Then parameters related to flowering, including the number of male and female flowers per inflorescence, by branch and tree were determined. The results showed in the South, which is relatively humid with a better distribution of rains than the North, the development of plants was the best. The AC1 accession of Sinématiali was well-suited to both cultivation sites. The most successful accessions in terms of growth in the North zone are AC1 from Sinématiali and AC6 from Toumodi. In the South, AC1 from Sinématiali and AC10 from Abengourou proved most suitable in term of adaptability.